1999
DOI: 10.1042/bj3390481
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix and integrin signalling: the shape of things to come

Abstract: The extracellular matrix (ECM) and integrins collaborate to regulate gene expression associated with cell growth, differentiation and survival. Biochemical and molecular analyses of integrin signalling pathways have uncovered several critical cytoplasmic proteins that link the ECM and integrins to intracellular pathways that may contribute to anchorage-dependent growth. A large body of evidence now indicates that the non-receptor protein kinases focal adhesion kinase (FAK) and specific members of the mitogen-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
0
11

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 422 publications
(170 citation statements)
references
References 95 publications
4
139
0
11
Order By: Relevance
“…Periostin is a member of a subset of secreted ECM-associated molecules termed "matri-cellular" proteins [48][49][50] that modulate interactions with structural components of the ECM, such as collagens, and a variety of cell surface receptors, such as integrins, to regulate cellular differentiation in development [51] and connective tissue disease [52]. Based on these data and numerous studies demonstrating that the ECM can potently regulate cellular differentiation [53][54][55][56][57], where possible we incorporated our periostin treatments into the collagen substrate, rather than simply amending the tissue culture media, to more closely replicate in vivo conditions. Periostin has been shown to promote collagen fibrillogenesis and alter the deposition of ECM proteins in other systems [58] and larger scale microarray studies have identified COL1A1 mRNA, encoding the collagen α1 component of heterotrimeric and homotrimeric type-1 collagen [59], as up-regulated in DD cord [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Periostin is a member of a subset of secreted ECM-associated molecules termed "matri-cellular" proteins [48][49][50] that modulate interactions with structural components of the ECM, such as collagens, and a variety of cell surface receptors, such as integrins, to regulate cellular differentiation in development [51] and connective tissue disease [52]. Based on these data and numerous studies demonstrating that the ECM can potently regulate cellular differentiation [53][54][55][56][57], where possible we incorporated our periostin treatments into the collagen substrate, rather than simply amending the tissue culture media, to more closely replicate in vivo conditions. Periostin has been shown to promote collagen fibrillogenesis and alter the deposition of ECM proteins in other systems [58] and larger scale microarray studies have identified COL1A1 mRNA, encoding the collagen α1 component of heterotrimeric and homotrimeric type-1 collagen [59], as up-regulated in DD cord [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Integrins can facilitate cell adhesion to extracellular matrix components as well as other cells. [185,196] The extracellular matrix, a naturally occurring multivalent display, may therefore also influence integrin activity. [197] In one study, surfaces were modified with peptide REs of different valencies for use in cell adhesion studies.…”
Section: 1a Integrins-integrinsmentioning
confidence: 99%
“…One of the major transducers of ECM/integrinderived signals is the focal adhesion kinase (FAK), a 125-kDa nonreceptor tyrosine kinase that can bind to, and phosphorylate, a number of intracellular signaling molecules, including Src, paxillin and p130cas, and mediate downstream activation of phosphatidylinositol 3-kinase and mitogen-activated protein kinase signaling through a network of adaptor proteins (reviewed in Boudreau andJones, 1999 andSastry andBurridge, 2000). Increased FAK expression and/or activation have been documented in various malignancies and shown to correlate with the invasive/metastatic phenotypes of the cells (reviewed in Gabarra-Niecko et al, 2003 andKahana et al, 2002).…”
Section: Introductionmentioning
confidence: 99%